2014
DOI: 10.12688/f1000research.5131.1
|View full text |Cite
|
Sign up to set email alerts
|

Difficult mask ventilation in general surgical population: observation of risk factors and predictors

Abstract: Background: There are few predictors of difficult mask ventilation and a simple, objective, predictive system to identify patients at risk of difficult mask ventilation does not currently exist. We present a retrospective - subgroup analysis aimed at identifying predictive factors for difficult mask ventilation (DMV) in patients undergoing pre-operative airway assessment before elective surgery at a major teaching hospital. Methods: Data for this retrospective analysis were derived from a database of airway as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…15,27 The lack of increase in genitourinary complications throughout all multimodal categories should also be noted, in light of the fact that complementary use of drugs such as NSAIDs, COX-2 inhibitors, and paracetamol/acetaminophen, have been associated with their own risks, including renal toxicity. 29,30 Notably, multimodal analgesia was also associated with a stepwise, continuous decrease in LOS by up to 11.8%, while a negligible effect was observed for cost of hospitalisation. The decrease in LOS, cost, and gastrointestinal complications with the use of multimodal analgesia could be related, given a recent population-based analysis in OSA patients demonstrating reduced odds for these complications at lower vs higher perioperative opioid dose concentrations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…15,27 The lack of increase in genitourinary complications throughout all multimodal categories should also be noted, in light of the fact that complementary use of drugs such as NSAIDs, COX-2 inhibitors, and paracetamol/acetaminophen, have been associated with their own risks, including renal toxicity. 29,30 Notably, multimodal analgesia was also associated with a stepwise, continuous decrease in LOS by up to 11.8%, while a negligible effect was observed for cost of hospitalisation. The decrease in LOS, cost, and gastrointestinal complications with the use of multimodal analgesia could be related, given a recent population-based analysis in OSA patients demonstrating reduced odds for these complications at lower vs higher perioperative opioid dose concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…2e4 Moreover, OSA has been linked to an increased risk for the presence of a difficult airway. 29,30 This is important, as the postoperative period is crucial given the exacerbation in sleep disordered breathing 31 at a time of highest levels of pain and analgesic requirement. Chung and colleagues 31 demonstrated that cumulative 72-h opioid dose appears to independently drive a higher postoperative apnoea-hypopnoea index, while others have described possible alterations in pain sensitivity and augmented opioid potency in OSA.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective investigation was performed to identify predictive markers of DMV in obese patients at Memorial Hermann Hospital-Texas Medical Center utilizing an existing database of airway assessment and airway management records 4 , 14 : 1399 anesthetics were identified where both mask ventilation was attempted and a pre procedure airway evaluation was documented. Of these, 557 obese patients were identified and included for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Bag mask ventilation commonly precedes the establishment of a secure airway by endotracheal intubation. However, the degree of difficulty encountered is variable 1 4 , with the incidence of Difficult Mask Ventilation (DMV) varying from 0.08–15% depending on the criteria used for the definition. The American Society of Anesthesiologists’ (ASA) original definition recognized DMV as a situation where it is not possible for the unassisted anesthesiologist to maintain the oxygen saturation > 90% using 100% oxygen and positive pressure ventilation, or to prevent or reverse signs of inadequate ventilation 5 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Patient characteristics that create higher rates of BMV difficulty include facial hair, lack of teeth, large neck circumference, obesity, sleep apnea, excessive pharyngeal tissue, inability to flex or extend the head, mandibular immobility, and old age. 7,9,10 Using a two-handed mask-face sealing technique has demonstrated the greatest success in delivering consistent, adequate tidal volumes during BMV in difficult patients as well as in the emergency department and out-of-hospital situations. 11,12 Documented complications of BMV are gastric inflation and aspiration of stomach contents.…”
Section: To the Editormentioning
confidence: 99%